Consider this system of equations: 23x+35y=12 (equation A) 52y−3x=6 (equation B) The expression that gives the value of x is . The solution for the system of equations is

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Consider this system of equations: 23x+35y=12 (equation A) 52y−3x=6 (equation B) The expression that gives the value of x is . The solution for the system of equations is

Algebra
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Welcome to OpenStudy! @helpstudy112 Do you know how to solve by substitution, elimination, or by graphing?
23x+35y=12;−3x+52y=6 Step: Solve 23x+35y=12 for x: 23x+35y+−35y=12+−35y(Add -35y to both sides) 23x=−35y+12 23x23=−35y+1223(Divide both sides by 23) x=−3523y+1223 Step: Substitute (−3523y+1223) for x in −3x+52y=6: −3x+52y=6 −3(−3523y+1223)+52y=6 130123y+−3623=6(Simplify both sides of the equation) 130123y+−3623+3623=6+3623(Add 36/23 to both sides) 130123y=17423 130123y130123=17423130123(Divide both sides by 1301/23) y=1741301 Step: Substitute (1741301) for y in x=−3523y+1223: x=−3523y+1223 x=−3523(1741301)+1223 x=4141301(Simplify both sides of the equation) Answer: x=414/1301 and y=174/1301
thank you

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Not the answer you are looking for?

Search for more explanations.

Ask your own question